Emergency department attendance following 4-component meningococcal B vaccination in infants. Issue 10 (21st June 2017) - Kapur, Sarah; Bourke, Thomas; Maney, Julie-Ann; Moriarty, Paul
Abstract : Introduction: In September 2015, the UK became the first country in the world to introduce the 4-component meningococcal B vaccine(4CMenB) into the routine vaccine schedule for infants. 4CMenB is known to cause fever in infants. Infants presenting with fever, particularly those under 3 months, have a significant risk of serious bacterial infection(SBI). Method: Between September 2015 and January 2016, we performed a prospective audit of management of infants between 30 and 180 days attending the regional paediatric emergency department(ED) in Northern Ireland, within 4 days of receiving 4CMenB. Results: 35 ED attendances in infants aged 30–180 days were due to symptoms occurring after primary vaccinations including 4CMenB, representing an estimated 0.8% of the vaccinated population in the catchment area. 86% of infants presented after the first vaccine and parents reported giving paracetamol to 94% of infants. 80% of infants presented with fever. Blood tests were performed in 62% of infants and leucocytosis was present in 73%. All cultures taken were negative and 51% were admitted to hospital. 100% of final diagnoses were vaccine related (diagnosis made by exclusion). Discussion: In this study, an estimated 0.8% of the vaccinated population in the catchment area attended ED with symptoms occurring after primary vaccinations including 4CMenB. Infants with fever have a higher risk of SBI, but infants with fever in the post-vaccination period may not have the same risk. Further data are essential to inform national guidelines on investigation and management of fever in infants following vaccination with 4CMenB, possibly incorporating a less-invasive approach.